Pengaruh Berat Pecahan Arang Kelapa yang berbeda sebagai Filter dalam Mempertahankan Kualitas Air pada Pemeliharaan Benih Ikan Kakap Putih (Lates calcarifer) - Muhammad Aulia Zuber Matondang; Henky Irawan; Tri Yulianto (Intek Akuakultur, 2021)
The research was carried out in September 2021, taking place at the Marine Aquaculture Laboratory and for water quality analysis carried out at the Marine Chemitry Laboratory of the Raja Ali Haji Maritime University, Tanjungpinang City, Riau Islands Province. The method used is an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications. The results showed that the levels of ammonia and nitrite decreased after passing through the coconut shell charcoal fragments. The best reduction in ammonia and nitrite levels was obtained in treatment C (using coconut charcoal fragments of 30 g/liter of rearing container water), resulting in total ammonia nitrogen of (11,983±0.691) and nitrite (4.14±0.01), the length of time for filter performance for 2 days the level of ammonia (0.115±0 ppm) and nitrite level of (4.448±0)